Putting the 'Street' in Gang: Place and Space in the Organization of Scotland's Drug-Selling Gangs. (5th September 2018) - McLean, Robert; Deuchar, Ross; Harding, Simon; Densley, James
Abstract: Street gangs, by definition, enjoy a special relationship with the street. Prior research shows that some communities are synonymous with gangs and that turf holds a combination of expressive and instrumental value for gang members. As gangs evolve over time and through different levels of organization, however, gangs' relationship with the street changes. This shifting street dynamic is underexplored in prior research, thus, drawing on qualitative data from Scotland and Bourdieu's theory of social field, the current study presents three cases of gangs at different stages of evolution and examines how levels of gang organization affect spatial relationships. As gangs accumulate sufficient street capital to evolve, we find territory is defined less physically and more relationally, with implications for gang research and practice.